Foveal Avascular Zone in Normal Tension Glaucoma Measured by Optical Coherence Tomography Angiography. (17th December 2017) - Zivkovic, Maja; Dayanir, Volkan; Kocaturk, Tolga; Zlatanovic, Marko; Zlatanovic, Gordana; Jaksic, Vesna; Radenkovic, Marija; Jovanovic, Predrag; Sefic Kasumovic, Sanja; Golubovic, Mladjan; Jovanovic, Svetlana
Abstract : Aim . To measure diameter of foveal avascular zone (FAZ), FAZ area, and vessel density using Optical Coherence Tomography Angiography (OCT-A) in patients with normal tension glaucoma (NTG) and to establish the possible role of OCT-A in diagnosis and follow-up of patients with NTG. Methods . Twenty-one eyes of 21 patients with NTG and 30 eyes of 30 healthy subjects underwent complete ophthalmic examination as well as OCT-A on ZEISS AngioPlex. 3 × 3 macula scans were used to measure vertical, horizontal, and maximum diameter of FAZ by two graders. Mean values and interobserver variability were analyzed. Image J was used for analysis of FAZ area and vessel density. Results . Mean vertical diameter (t = 5.58, p < 0.001 ), horizontal diameter (t = 3.59, p < 0.001 ), maximum diameter (t = 5.94, p < 0.001 ), and FAZ area (t = 5.76, p < 0.001 ) were statistically significantly enlarged in the NTG group compared to those in the control group. Vessel density (t = - 5.80, p < 0.001 ) was statistically significantly decreased in the NTG group compared to that in the control group. Conclusion . OCT-A could have an important role in the future in diagnosis of patients with NTG. In patients with NTG, there is larger FAZ area, while the vessel density is reduced in comparison to the control group.